Characteristics and determinants of community physiotherapy utilization and supply - Chidozie Mbada; Abraham Olawuyi; Olufemi O. Oyewole; Adesola C. Odole; Abiola O. Ogundele; Francis Fatoye (BMC, 2019)
Abstract Background Demand for Physiotherapy is on the rise due to increasing ageing population and consequent disability and morbidity. However, the costs of healthcare in developing countries are rising, and healthcare resources are limited making the supply of Physiotherapy services challenging in rural communities. Availability of Physiotherapy may help to reduce the burden of disability and enhance efficiency of healthcare systems. This study investigated the characteristics and associations of utilization and supply of community Physiotherapy in Nigeria. Methods Cross-sectional survey of 336 consenting community dwelling individuals from three selected communities in Nigeria was carried out. A three-section validated self-developed questionnaire which sought information on socio-demographics, utilization and supply of community Physiotherapy, as well as how to improve community Physiotherapy services was used. A household was used as the primary sampling unit in the study. Inferential and Descriptive statistics were used to assess the data. Results Lifetime, 12-month and point utilization of physiotherapy was 21.7, 7.4 and 2.7% respectively. Physiotherapy utilization was significantly associated with level of education (p = 0.007), belief on pain as "spiritual" (p = 0.020) and religious belief (p = 0.001). The respondents with primary, secondary and tertiary education were 14.3, 13.9 and 26 times more likely to utilize physiotherapy services, respectively. Those who 'agree' or were 'not sure' that their religious belief was against physiotherapy were 92 and 83% less likely to utilize physiotherapy services, respectively compared with those who 'disagree'. Availability and supply of Physiotherapy services were mostly at the township teaching hospital (47.9%) and private hospitals (20.5%). The supply of Physiotherapy services within the communities was mostly on temporary basis (24.7%) and through visiting Physiotherapists (21.4%). Physiotherapy services utilized was mainly exercise (46.6%) and soft tissue mobilization (41.1%). Travel costs (32.6%), time constraints (27.9%) and work commitments (24.8%) were the constraints for Physiotherapy utilization while positive beliefs and higher education improved Physiotherapy utilization. Conclusions Utilization and supply of Physiotherapy services in Nigerian rural community was low. Low utilization of Physiotherapy services in Nigerian rural communities were most significantly influenced by low educational status and beliefs about pain.